Ensino de inglês sob a perspectiva decolonial: uma proposta de sequência didática - Menegat, Isabella Cristina (2024)
This work aims to propose a didactic sequence that aligns English language teaching with decolonial theories. To this end, we will discuss the concepts of colonialism and coloniality (Quijano, 2009; Grosfoguel, 2016), considering the National Common Curricular Base (Brazil, 2018), and culminating in the proposal of the didactic sequence (Dolz and Schneuwly, 2004). For this purpose, we use bibliographic and documentary research with qualitative data. As a preliminary result, we highlight the enrichment of pedagogical practice by aligning decolonial theories with the formulation of didactic sequences.